The (Null) Effect of Affective Touch on Betrayal Aversion, Altruism, and Risk Taking - Koppel, Lina; Andersson, David; Morrison, India; Västfjäll, Daniel; Tinghög, Gustav (Frontiers in Behavioral Neuroscience, 2017)
Pleasant touch is thought to increase the release of oxytocin. Oxytocin, in turn, has been extensively studied with regards to its effects on trust and prosocial behavior, but results remain inconsistent. The purpose of this study was to investigate the effect of touch on economic decision making. Participants (n = 120) were stroked on their left arm using a soft brush (touch condition) or not at all (control condition; varied within subjects), while they performed a series of decision tasks assessing betrayal aversion (the Betrayal Aversion Elicitation Task), altruism (donating money to a charitable organization), and risk taking (the Balloon Analog Risk Task). We found no significant effect of touch on any of the outcome measures, neither within nor between subjects. Furthermore, effects were not moderated by gender or attachment. However, attachment avoidance had a significant effect on altruism in that those who were high in avoidance donated less money. Our findings contribute to the understanding of affective touch—and, by extension, oxytocin—in social behavior and decision making by showing that touch does not directly influence performance in tasks involving risk and prosocial decisions. Specifically, our work casts further doubt on the validity of oxytocin research in humans.